Taboo Words Analysis in Fast and Furious 8 Movie by F. Gary Gray - Narti Septia (MEDIOVA: Journal of Islamic Media Studies, 2023)
This study analyzes the taboo words in Fast and Furious 8 movie by F. Gary Gray. Taboo words occur not only in everyday life but also in the movie. This study aims to investigate the types of taboo words using the theory of Jay (1992) and the functions of taboo words using Wardhaugh's theory (2006). This study employed a descriptive qualitative as a research method. The result of this study shows there are seven types of taboo words, namely cursing 17 data, profanity 9 data, obscenity 1 data, epithet 15 data, vulgarity 14 data, insult and slur 7 data, and scatology 6 data. Then, there are four functions of taboo words, namely to draw attention 42 data, to show contempt 16 data, to be provocative 10 data, and to mock authority 1 data. Based on the analysis results, the word hell appears to be the second most taboo word used in this movie and has become the most dominant type of taboo word, namely cursing. This is because they use cursing to express their feelings, such as anger, annoyance, or shock, and to emphasize something in an utterance. Furthermore, all the words hell in this movie have the function as to draw attention. To draw attention appears as the most dominant function in Fast and Furious 8 movie because it can represent the character's intention of using taboo words.